STRATEGY FORMULATION IN ENCOURAGING COMMUNITY DEVELOPMENT OF GEOPARK CILETUH-PALABUHANRATU SUKABUMI - Widhikora, Destria Arundani; Hudrasyah, Herry (Journal of Business and Management, 2017)
Abstract. Ciletuh-Palabuhanratu Geopark is a tourism destination in Sukabumi district which is relied by the government of West Java to hold UNESCO Global Geopark status by the year 2018. However, for the geopark to be recognized as such, it needs to pass the requirements set by UNESCO, which is to develop the geopark area using sustainability concept and community development in mind. All these three aspects; economical, socio-cultural, and environmental, should be sustainably managed. This research aims to explore new strategies for CPG management in the cause of sustainably developing Ciletuh-Palabuhanratu community areas. In-depth interview, journal and article study are used as main data collection methods. Environmental scanning is conducted before strategic formulation using SWOT Analysis, TOWS Matrix, and Porter’s Generic Competitive Advantage. External analysis found that trend of ecotourism and the use of internet for tourism is rising, community members are mostly cooperative yet lacking in education about conservation, geopark vision, and foreign language. Internal analysis found that geopark has many diversities, strong government ties, and team of experts, but their problems are lack of infrastructure and public business facility and threat from illegal mining. Keywords: community development, Geopark Ciletuh-Palabuhanratu, local community, strategy formulation, sustainability